2017
DOI: 10.1097/md.0000000000009349
|View full text |Cite
|
Sign up to set email alerts
|

Central vestibular disorder due to ischemic injury on the parieto-insular vestibular cortex in patients with middle cerebral artery territory infarction

Abstract: Central vestibular disorder is common after middle cerebral artery (MCA) territory infarction. The MCA supplies blood to the parieto-insular vestibular cortex (PIVC), a core region of central vestibular symptoms. We report on patients that sustained injuries of the core vestibular pathway to the PIVC with central vestibular disorder following MCA territory infarction, demonstrated on diffusion tensor imaging (DTI). Nineteen patients with MCA territory infarction and 12 control subjects were recruited. To recon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
19
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 35 publications
(31 reference statements)
0
19
0
Order By: Relevance
“…One analyzer (Kwon HG) performed fiber tracking using probabilistic tractography, which was applied in the default tractography option (5000 streamline samples, 0.5 mm step lengths, curvature thresholds = 0.2) of the Oxford Centre for FMRIB Software Library [35,36]. The CVP was reconstructed from a seed region of interest at the VN corresponding to Schwalbe's and Deiters' nuclei at the pons level [31]. The target region of interest was positioned at the PIVC [31].…”
Section: Diffusion Tensor Tractographymentioning
confidence: 99%
See 2 more Smart Citations
“…One analyzer (Kwon HG) performed fiber tracking using probabilistic tractography, which was applied in the default tractography option (5000 streamline samples, 0.5 mm step lengths, curvature thresholds = 0.2) of the Oxford Centre for FMRIB Software Library [35,36]. The CVP was reconstructed from a seed region of interest at the VN corresponding to Schwalbe's and Deiters' nuclei at the pons level [31]. The target region of interest was positioned at the PIVC [31].…”
Section: Diffusion Tensor Tractographymentioning
confidence: 99%
“…The CVP was reconstructed from a seed region of interest at the VN corresponding to Schwalbe's and Deiters' nuclei at the pons level [31]. The target region of interest was positioned at the PIVC [31]. The core vestibular projection passes from the vestibular nuclei at the level of the pons to the PIVC via the posterolateral thalamus [9].…”
Section: Diffusion Tensor Tractographymentioning
confidence: 99%
See 1 more Smart Citation
“…For an imaging-based reconstruction of the core vestibular projection, the seed region of interest was placed on the vestibular nuclei that corresponded to Schwalbe's and Deiters' nuclei at the pons level [2][3][4]. The target region of interest was positioned at the parieto-insular vestibular cortex (PIVC) [2][3][4]. The core vestibular projection passes from the vestibular nuclei at the level of the pons to the PIVC via the posterolateral thalamus [2].…”
mentioning
confidence: 99%
“…Two studies using DTT have reported on core vestibular projection injuries following a cerebral infarct [4,13]. In 2017, Yeo et al demonstrated that core vestibular projection injuries were associated with central vestibular disorders in 19 patients with middle cerebral artery territory infarctions [4].…”
mentioning
confidence: 99%